Kolehiyo ng agham: Isang pagsulong ... - College of Science (Animo Repository, 1994)
The DLSU College of Science celebrated its COS Week from September 26 to October 1. The theme of the celebration was Kolehiyo ng Agham: Isang Pagsulong... It started off with a Mass celebrated at the Chapel of the Pearl of Great Price at 9:00 a.m.